2007
DOI: 10.1108/00400910710729857
|View full text |Cite
|
Sign up to set email alerts
|

The use of animation in higher education teaching to support students with dyslexia

Abstract: PurposeThe purpose of the research reported in this paper was to examine the potential usefulness of animated learning materials for supporting students with dyslexia in a UK higher education setting.Design/methodology/approachAn experiment was conducted with a set of 13 undergraduate computing students with dyslexia and a control group of 13 non‐dyslexic undergraduate computing students.FindingsOverall it appeared that appropriate animated learning materials were perceived as being more useful than equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
3
12
1
Order By: Relevance
“…This conclusion comes from the fact that 67% of respondents indicated that animations and simulations in courses enabled them to grasp difficult concepts more easily. This finding is inline with what other researchers also found such as [9], [14], [23], [12] and [10] regarding the benefits of animations and simulations help students grasp difficult concepts.…”
Section: Discussion and Lesson Learntsupporting
confidence: 94%
“…This conclusion comes from the fact that 67% of respondents indicated that animations and simulations in courses enabled them to grasp difficult concepts more easily. This finding is inline with what other researchers also found such as [9], [14], [23], [12] and [10] regarding the benefits of animations and simulations help students grasp difficult concepts.…”
Section: Discussion and Lesson Learntsupporting
confidence: 94%
“…This finding was in harmony with what suggested by the previous studies and researches in the field of the use of visual stimuli in the achievement of the cognitive aspects, one of these studies is the one prepared by Grabowski, 2004)), Joseph (2006), Fath Allah (2007), Hughes, 2007), (Stavy, 2008), (Tibell, 2010), whereas this research finding differs with that of finding of Al-Sarraf (1998), and Khalaf Allah (2010).…”
Section: Discussioncontrasting
confidence: 50%
“…The instructional design model is a combination of procedure used to create an effective product in order to achieve the learning objectives that have been formulated [8]- [10]. Manuscript This argument is in line with [11], [12] which stated that a good courseware design would be able to contribute towards an encouraging learning outcome. Hence, in ensuring that the courseware design is accurate and suitable, the adequate instructional design model should be identified before the development process begins.…”
Section: Introductionmentioning
confidence: 84%